Recent works on microbes and infections in China : selected from the Journal of Microbes and Infections (China) - Wen, Yu-Mei; World Scientific (Firm) (Singapore ; Hackensack, N.J. : World Scientific Pub. Co., 2010)
Microbial infections have been and continue to be a major threat to public health. China has a huge population, among which, microbial infections are of great concern. The Journal of Microbes and Infection, a nationwide journal in China with over 4000 subscriptions, publishes original research articles on microbes and infections in the Chinese language. This book contains selected research articles published in this journal from 2006 to 2007 that have been translated into English, and offers a glimpse of a broad range of microbial infections including the clinical and epidemiological aspects of various viral infections, current status of bacterial infections in hospitals, and severe cases of fungal infections. This book provides a rare opportunity for scientists and physicians abroad to see the completely original research data, rather than just the abstract, based on studies conducted in modern China. Articles on molecular biological and bioinformatic studies are also included. An overview of the recent research trend in medical microbiology and infectious diseases in China will be presented as well. Scientists and physicians working in the fields of virology, microbiology, immunology, epidemiology, vaccinology, and infectious diseases will find the articles in this book fascinating and relevant to their own research and practice.
Section 1. Bacteria. Introduction and comments : studies on bacteria by molecular and experimental approaches / Yu-Mei Wen -- 1.1. Cloning, expression and immunological evaluation of a novel protein belonging to the OmpA family in Leptospira interrogans / Wei Lin [and others] -- 1.2. Surveillance of Leptospirosis and the Murine Reservoirs in China, 2005 / Xiu-Gao Jiang [and others] -- 1.3. Cloning and expression of the histidinol dehydrogenase gene from mycobacterium tuberculosis H37Rv and properties of the recombinant histidinol dehydrogenase / Rui-Liang Jin [and others] -- 1.4. Cloning and sequence analysis of the fbps gene of Streptococcus suis Type 2 / Li-Yun Sun, Hong-Jie Fan and Cheng-Ping Lu -- 1.5. Effects of EnvZ histidine kinase inhibitors on the virulence of Shigella flexneri / Ming-Liang Chen [and others] -- 1.6. Detection of virulence and genes for viable but nonculturable (VBNC) Campylobacter jejuni / Jie-Lin Yang [and others] -- Section 2. Viruses. Introduction and comments : trends on virus research in China / Yu-Mei Wen -- 2.1. Transcriptomic and proteomic studies on HBsAg-positive transgenic mouse livers suggest alterations in carbohydrate, lipid and amino acid metabolism / Jun Ren [and others] -- 2.2. Large-scale polymorphism analysis of hepatitis B virus envelope protein using bioinformatics / Zhe Chen [and others] -- 2.3. Studies on the inactivation of hepadnavirus in blood components by using a duck hepatitis B virus-infected animal model / Wen-Yi Wang [and others] -- 2.4. Sequence analysis of the SH gene and its flanking region of a mumps virus strain (SP strain) / Shao-Hui Ma [and others] -- 2.5. HIV-related knowledge, attitudes and behaviors among policewomen and female prisoners from a Behavior Correction Center / Wei Jiao [and others] -- Section 3. Laboratory medicine. Introduction and comments : advances and trends in diagnostic microbiology in China / Yi-Wei Tang -- 3.1. Detection of SARS-associated coronavirus infection by reverse transcriptase-polymerase chain reaction, indirect immunofluorescence assay and enzyme-linked immunosorbent assay / Zhi-Tong Zhou [and others] -- 3.2. Bacteriological and molecular identification of a sporadic case of brucellosis in Shanghai / Cheng-Yan Meng [and others] -- 3.3. A PCR-capillary electrophoresis method detects and differentiates biovars of Ureaplasma urealyticum / Shi-Hang Zhou and Zhuo-Ran Zhang -- 3.4. Implications of CD64 in early diagnosis of neonatal septic cases / Rong Zhang and Chao Chen -- 3.5. Correlation between the MICA*A5.1 allele and Chlamydia trachomatis infection / Bing Mei [and others] -- 3.6. Surveillance of human infections with avian influenza in Guangzhou during 1997-2006 / Peng-Zhe Qin [and others] -- 3.7. Clinical significance of human cytomegalovirus pp65-specific antibodies for verification of HCMV primary infection / Qian Liu, Jing-Xian Chen and Ming-Li Wang -- 3.8. Analysis of indeterminate HIV Western blot profiles / Kai Gao [and others] -- 3.9. Detection of multidrug-resistant Mycobacterium tuberculosis by sputum smears / Shu-Yan Wu, Guo-Hao Gu and Rui Huang -- Section 4. Clinical medicine. Introduction and comments : a glimpse of clinical infectious diseases in China in the new millennium / Shan Lu -- 4.1. The role of lower airway bacterial colonization at the stable stage of chronic obstructive pulmonary disease / Min Zhang [and others] -- 4.2. Gene sequence analysis of the norovirus detected in diarrhea specimens from children in a Surveillance Hospital in Shanghai / Zheng Teng [and others] -- 4.3. Clinical analysis of 77 measles patients / Dong-Mei Shi and Qing Xie -- 4.4. Analysis of clinical characteristics in 77 HIV-infected individuals / Qi-Ming Gong [and others] -- 4.5. Etiology and clinical characteristics of children hospitalized for acute lower respiratory tract infection in winter / Jun Shen [and others] -- 4.6. Infectious disease risks associated with the Sichuan earthquake : experiences in treatment of earthquake wound infections / Xin Zhao [and others] -- Section 5. Immunology and vaccinology. Introduction and comments : exploring host immune responses to microbes / Shan Lu -- 5.1. Detection of dendritic cell subsets in peripheral blood and levels of IL-12 and IFN-[symbol] in serum of patients with syphilis / Li-Xiong Zheng [and others] -- 5.2. Analysis of antigenicity and immunogenicity of the receptor-binding domain of SARS-CoV / Ping Zhao [and others] -- 5.3. Alterations in Chemokine expression in PBMCs during and after interferon-[symbol] therapy in HCV chronic infections / Yun-Wen Hu [and others] -- 5.4. A summary of immunogenicity studies on DNA vaccines expressing the hepatitis B virus core and surface antigens as tested in both murine and nonhuman primate models / Yi-Ping Xing [and others].
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Virology -- Research -- China; Communicable diseases -- Research -- China; Virologie -- Recherche -- Chine; Maladies infectieuses -- Recherche -- Chine; SCIENCE -- Life Sciences -- Biology; SCIENCE -- Life Sciences -- Microbiology; Communicable diseases -- Research; Virology -- Research; China